PROCESSING PALM OIL AND COCONUT OIL INTO BAR SOAP WITH PAPAYA EXTRACT - salsa nabilla (SEMESTA: Journal of Science Education and Teaching, 2023)
Soap, as a cleaning agent, is produced through a saponification reaction between oil and a strong base (NaOH), producing glycerol as a by-product. In this case, experiments were carried out using the cold process method to explore making soap with the addition of papaya extract. This research also involves analyzing the quality of soap through organoleptic tests and acidity degree (pH) analysis. The organoleptic test results showed that the soap had an appropriate texture, sufficient foam, and an attractive color after dyeing. Implementation of the saponification reaction with NaOH requires precision and accuracy of measurements for the success of the process. Apart from that, the use of essential oils and the proportion of NaOH affect the quality of the soap. The curing process is carried out for ± 30 days to optimize the quality of the soap. This research aims to produce good quality soap, with a focus on evaluating organoleptic tests and acidity levels as indicators of success.